Splice strength of deformed steel bars embedded in recycled aggregate concrete. (May 2017) - Robert Prince, M. John; Gaurav, Govind; Singh, Bhupinder
Abstract: Splice strength of deformed steel bars embedded in recycled aggregate concrete was experimentally investigated using 24 bottom-cast scaled splice beam specimens detailed with unconfined contact lap splices and tested under four-point bending. The following variables were investigated: concrete grade (normal- and high-strength), recycled concrete aggregate replacement level (0%, 50% and 100%), rebar diameter (12 mm and 20 mm) and rebar surface characteristics. Bond behaviour and failure modes were noted to be similar in the natural and in the recycled aggregate concrete and a regression analysis of the results shows that f c ′1/4 provides a good representation of the influence of recycled aggregate concrete grade on splice strength. A descriptive bond strength equation has been proposed for recycled aggregate concrete and it is noted that the ACI Committee 408R-03 model (for conventional concrete) gave relatively the most accurate and conservative bond strength predictions for the recycled aggregate concretes under investigation.